Korelasi Dimensi Ukuran-Ukuran Tubuh Terhadap Bobot Badan, Karkas dan Daging Sapi Bali di Rumah Potong Hewan (RPH) Kabupaten Kolaka - Bukit Aprilliawan; Harapin Hafid; Amiluddin Indi (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2024)
Meat is an animal food popular with all levels of society because it tastes delicious and contains high nutritional value. This study aimed to determine the correlation between body size dimensions and body weight, carcass, and meat in Bali cattle. This study was conducted at the Kolaka Regency Slaughterhouse (RPH), with the research object being Bali cattle aged ≥ 3 > 6 years, as many as 50 heads. The variables in this study consisted of Body weight, Carcass percentage, Meat percentage, Carcass length, Chest circumference, Chest depth, Thigh length, and Thigh circumference. Furthermore, the data were analyzed using multiple linear regression analysis. The results showed that the correlation coefficient (r) between body measurements and Bali cattle's body weight, carcass, and meat varied. The variable between carcass length and the carcass had the lowest relationship, with an R-value of 0.363. At the same time, the variables that had a very strong relationship were the chest circumference and body weight variables, with an r-value of 0.928. In addition, the study's results also showed that the regression coefficient (Y, W, Z) of each body size in Bali cattle had a significant impact on body weight, carcass, and meat of Bali cattle. The chest circumference and thigh length factors directly influenced body weight, carcass, and meat.